(untitled) (Research, Society and Development, 2021)
In this project, tests were carried out on aqueous compounds with alcohol smoke extract (Nicotiana tabacum), castor bean extract (Ricinus communis), kassod tree leaf extract (Senna siamea), for the control of aphids in the organic cultivation of broccoli (Brassica oleracea var. Italica) and cauliflower (Brassica oleracea var. Botrytis). Where it was held inside Reserva / PR. The test of three beds with 12 broccoli plants with the smoke extract with alcohol, three beds with the castor extract was carried out, and three beds with the castor extract, three beds with the leaf extract of (Senna siamea) and three control beds without extracts, the measurements between plants were 60 cm, the beds were 1.20m wide by 2m long with 50 cm spacing between each other. Where the beds were placed in a random order. In winter, branch broccoli cultivar Santana was implanted and in summer cauliflower cultivated giant Teresópolis, both cultures with the same system. With the end of the experiment, variables with significant results were obtained, for broccoli we had total mass and insect control with Senna siamea leaf extract and castor extract with higher averages, respectively, in the dry and fresh mass point by plants, the Senna siamea extract with superior efficacy with the other extracts in the cultivation of broccoli, in the culture of cauliflower the castor extract with superior efficacy in the control of insects, in relation to the dry mass of the inflorescence and the dry matter of the inflorescence tobacco extract with final efficacy, at the end of the experiments in relation to insect control of broccoli and cauliflower culture, castor bean extract was obtained with effectiveness in insect control. For greater efficiency of these plant extracts, more improved studies involving different concentrations of the extracts are recommended, in order to determine a more adequate proportion, which allows greater efficiency and control of this insect, which will result in the reduction of the use of synthetic insecticides for producers, results in reducing environmental impacts and production costs.